Immune responses to vaginal candidiasis in African women: A scoping review of cytokine profiles, T-cell activation, and gene expression. - Bwambale Jonani; Bwire Roman Herman; Joel Fredrick Arturo; Richard Kwizera; Gerald Mboowa; Felix Bongomin (PLoS ONE)
Background Recent immunological studies of vaginal candidiasis in African populations have revealed complex host‒pathogen interactions with implications for therapeutic development and HIV acquisition risk. Objective This scoping review synthesized evidence from Uganda, Zambia, South Africa, and Kenya between 2020 and 2024, focusing on immune responses, cellular dynamics, and tissue effects due vulvovaginal candidiasis. Results Analysis revealed a coordinated inflammatory response marked by elevated levels of the proinflammatory cytokines IL-1β and IL-6 and increased chemokine IL-8-mediated immune cell recruitment. Compared with those in control individuals, distinct T-cell population patterns in colonized individuals show reduced Th17-like CD4+ T-cell activation, with concurrent increases in Th1/Th2-enriched CD4+ T cells. Molecular analysis revealed that 162 differentially expressed genes were involved primarily in neutrophil-mediated immunity and cytokine signaling pathways. Despite robust immune activation, tissue integrity remained intact, accompanied by elevated antimicrobial peptides SLPI and BD-2. Notably, Candida-colonized individuals presented reduced frequencies of HIV target cells (CCR5 + HLA-DR + CD4 + T cells). Conclusion These findings advance our understanding of population-specific immune responses to vaginal candidiasis and identify promising therapeutic targets, highlighting the need for longitudinal studies to characterize vulvovaginal candidiasis immunopathogenesis fully in African populations.